Artificial Intelligence dan Kreatifitas Digital: Subyek Hukum dan Sarananya Dalam Perspektif Kekayaan Intelektual - Samsithawrati, Putu Aras (Kertha Patrika, 2023)
This article aims to analyze legal protection of creative works created by Artificial Intelligence (AI) from the perspective of Intellectual Property (IP) Law and future construction of IP law regarding works produced by AI. This article uses normative legal research methods with statutory, conceptual and analytical approaches. The results show that in the first pattern, creative work involves AI only as a supporting tool and humans take a full share in the production process of the work, then the work can be protected by IP law as long as it meets the legal object and subject checks based on statutory IP regulations. In the second pattern, if the creative work in the IP field is created entirely by AI then the work cannot be given legal protection in the IP realm because it can be interpreted that AI is the creator/inventor/designer and not humans. In this second pattern, although the object check is fulfilled, the legal subject check is not fulfilled because in general the IP laws and regulations in Indonesia stipulate that the legal subject must be a human and not AI. In the future, existing legislation in the field of IP needs to include several basic provisions such as (1) works that receive protection in the realm of IP are works produced by humans where the legal subject is humans and not AI; and (2) the use of AI as technology is to bring maximum benefits to human life and not actually harm or even shift human existence.